(3GdefJNH aj TQM dGejI GdYQHs - (3jMji Hf CHi Wi MejO Hf XGaQ Hf Ydj GdMdHj GdZSGfis; (3GdTfaQj Hf GdGhS Hf GdMLQs
(3ChdgG (B:s
(3GdMeO ddg GdYXje GdTCf CeG HYO aEfi CQZH Edi Gddg GdYXje Cf jhabfi deG MGhdJg , hjjSQ di eG QJHg , ef TQM cdeI GdTfaQi dGejI GdYQH s
(3BNQgG (B:s
(3bGd (B: (3hQKi GdTfaQi JCHW TQkG Hbhdg (B: (3Ydi GdTfaQi ZGOi GdZeGe hQGFM ZQjQ GdYdi hUjH GdeGA HGcQ Je GdcJGH s
(3GdfSNI HgG MhGTs
(3hgj ef cJH CejQ GdeDefjf RjOGf GdMSfis
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs